2017
DOI: 10.1111/jep.12691
|View full text |Cite
|
Sign up to set email alerts
|

Remote control improves quality of life in elderly pacemaker patients versus standard ambulatory‐based follow‐up

Abstract: Remote device monitoring has a significant impact on HRQoL in pacemaker patients, increasing its levels up to 6 months after implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
3
7
0
2
Order By: Relevance
“…On the other hand, in NORDLAND study the MLHF questionnaire score was improved in the studied groups (21.78% vs. 54.42%) and at 6 months there were statistically significant differences between the groups. These results were similar to those obtained in other studies in which HRQoL questionnaires for specific heart-diseases such as MLHFQ [ 30 ], AQUAREL [ 18 ], Duke Activity Status Index (DASI) [ 10 ] were improved. In all the studies, similar results have been found regardless their research design, either randomized or non-randomized.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…On the other hand, in NORDLAND study the MLHF questionnaire score was improved in the studied groups (21.78% vs. 54.42%) and at 6 months there were statistically significant differences between the groups. These results were similar to those obtained in other studies in which HRQoL questionnaires for specific heart-diseases such as MLHFQ [ 30 ], AQUAREL [ 18 ], Duke Activity Status Index (DASI) [ 10 ] were improved. In all the studies, similar results have been found regardless their research design, either randomized or non-randomized.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies [ 10 , 16 18 , 30 ] have assessed HRQoL in users with pacemakers. In these clinical trials, the SF-36 [ 16 , 17 , 30 ] and EQ5D [ 10 , 18 ] questionnaires were used to assess HRQoL. Results were improved but no significant differences between both groups in either the effectiveness or the safety of TM and HM were found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One longitudinal study conducted in Italy assessed two groups of individuals with a cardiac pacemaker, with and without remote follow-up, and verified that HRQoL assessed by the AQUAREL resulted in better scores obtained by the group with remote follow-up in the three first months of follow-up, especially in the domains Arrhythmia and Chest Discomfort. 21 Similar to this study's results, other studies using the AQUAREL to assess the HRQoL among patients with PPI report that the domain with the worst score was Dyspnea. All these studies, however, report the domain that was best rated as being Chest Discomfort, which diverges from this study's results, in which Arrhythmia was the domain best rated.…”
Section: /12supporting
confidence: 84%